HUBUNGAN LINGKUNGAN KELUARGA DENGAN HASIL BELAJAR SISWA KELAS TINGGI SD NEGERI 85 CACALEPPENG KABUPATEN SOPPENG - Sudarto, Sudarto; Rosmalah, Rosmalah; Zahrah Jamilah (Bajang Institute, 2025)
This study is a correlational study that aims to determine whether there is or there is not a relationship between the family environment and the learning outcomes of the high-grade students at SD Negeri 85 Cacaleppeng, Soppeng Regency. The sample in this study was all of 45 high-grade students, who were taken using a saturated sampling technique. Data collection was carried out through a questionnaire for the family environment variable and documentation of odd semester report card scores for the 2024/2025 academic year for the learning outcome variable. The data analysis technique used was inferential statistics through the Pearson Product Moment correlation test. Based on the results of the inferential statistical analysis, it was obtained: rcount> rtable (0.825> 0.294) at the significance level of 5%. Conclusion: there is a significant correlation between the family environment and the learning outcomes of high-grade students at SD Negeri 85 Cacaleppeng, Soppeng Regency and the correlation is positive and categorized as Very High